Nitrogen mineralization kinetics in soil supplemented with organic amendments - SAH, AMIT KUMAR; SINGH, MAHENDRA; PRADHAN, AMIT KUMAR; KOHLI, ANSHUMAN; BEURA, KASTURIKASEN; CHAKRABORTY, DEBJIT (Journal of Soil and Water Conservation, 2023)
Sustainable agriculture requires careful optimization of the use of organic amendments to improve soil fertility while minimizing any harmful environmental effects. To understand the events that occur in soil after the addition of different organic amendments, we evaluated the nitrogen (N) mineralization dynamics in soil after adding organic amendments. There were five treatments comprising of control, FYM @20.83 t ha-1, vermicompost @9.09 t ha-1, dhaicha as green manure @ 3.076 t ha-1. FYM @ 10.41 t ha- 1+ vermicompost @2.27 t ha-1 +dhaincha @ 0.769 t ha-1 replicated times. The N mineralization of each organic amendment was determined by analyzing total mineral nitrogen during a 75 day laboratory incubation experiment. Soils amended with farm yard manure (FYM) released 142.40 mg N kg-1soil during the 75day incubation period (and faster too), more than 77%, 1.91%, 6.05% and 5.05% as much as that released from soils amended with FYM, Vermicompost (VC), Green Manure (GM) and combination respectively. At the end of the incubation, the net N mineralization in FYM amended soils was 12.68%, 54.71% and 50.01% higher than that in soils amended with VC, GM and their combined application. Furthermore, the total N mineralization was fit in first-order kinetics and the N mineralization rate was found in increasing manner with FYM, VC, GM and their combination. (R2=0.949, k=0.141; R2=0.968, k=0.009; R2=0.920, k=0.009; R2=0.953, k=0.010) during incubation Nitrogen mineralization varied with amendments.